A novel mechanism for target gene-specific SWI/SNF recruitment via the Snf2p N-terminus. - Weider, Matthias; Schröder, Agnes; Klebl, Franz; Sauer, Norbert (Nucleic Acids Research, 2011)
Chromatin-remodeling complexes regulate the expression of genes in all eukaryotic genomes. The SWI/SNF complex of Saccharomyces cerevisiae is recruited to its target promoters via interactions with selected transcription factors. Here, we show that the N-terminus of Snf2p, the chromatin remodeling core unit of the SWI/SNF complex, is essential for the expression of VHT1, the gene of the plasma membrane H(+)/biotin symporter, and of BIO5, the gene of a 7-keto-8-aminopelargonic acid transporter, biotin biosynthetic precursor. chromatin immunoprecipitation (ChIP) analyses demonstrate that Vhr1p, the transcriptional regulator of VHT1 and BIO5 expression, is responsible for the targeting of Snf2p to the VHT1 promoter at low biotin. We identified an Snf2p mutant, Snf2p-R(15)C, that specifically abolishes the induction of VHT1 and BIO5 but not of other Snf2p-regulated genes, such as GAL1, SUC2 or INO1. We present a novel mechanism of target gene-specific SWI/SNF recruitment via Vhr1p and a conserved N-terminal Snf2p domain.

Elementary immunology: Na(+) as a regulator of immunity - Schatz, Valentin; Neubert, Patrick; Schröder, Agnes; Binger, Katrina; Gebhard, Matthias; Mueller, Dominik N.; Luft, Friedrich C.; Titze, Jens; Jantsch, Jonathan (Pediatric Nephrology, 2017)
The skin can serve as an interstitial Na(+) reservoir. Local tissue Na(+) accumulation increases with age, inflammation and infection. This increased local Na(+) availability favors pro-inflammatory immune cell function and dampens their anti-inflammatory capacity. In this review, we summarize available data on how NaCl affects various immune cells. We particularly focus on how salt promotes pro-inflammatory macrophage and T cell function and simultaneously curtails their regulatory and anti-inflammatory potential. Overall, these findings demonstrate that local Na(+) availability is a promising novel regulator of immunity. Hence, the modulation of tissue Na(+) levels bears broad therapeutic potential: increasing local Na(+) availability may help in treating infections, while lowering tissue Na(+) levels may be used to treat, for example, autoimmune and cardiovascular diseases.
EVALuna2:3894

High salt intake reprioritizes osmolyte and energy metabolism for body fluid conservation - Kitada, Kento; Daub, Steffen; Zhang, Yahua; Klein, Janet D.; Nakano, Daisuke; Pedchenko, Tetyana; Lantier, Louise; Larocque, Lauren M.; Marton, Adriana; Neubert, Patrick; Schröder, Agnes; Rakova, Natalia; et al. (Journal of Clinical Investigation, 2017)
Natriuretic regulation of extracellular fluid volume homeostasis includes suppression of the renin-angiotensin-aldosterone system, pressure natriuresis, and reduced renal nerve activity, actions that concomitantly increase urinary Na+ excretion and lead to increased urine volume. The resulting natriuresis-driven diuretic water loss is assumed to control the extracellular volume. Here, we have demonstrated that urine concentration, and therefore regulation of water conservation, is an important control system for urine formation and extracellular volume homeostasis in mice and humans across various levels of salt intake. We observed that the renal concentration mechanism couples natriuresis with correspondent renal water reabsorption, limits natriuretic osmotic diuresis, and results in concurrent extracellular volume conservation and concentration of salt excreted into urine. This water-conserving mechanism of dietary salt excretion relies on urea transporter-driven urea recycling by the kidneys and on urea production by liver and skeletal muscle. The energy-intense nature of hepatic and extrahepatic urea osmolyte production for renal water conservation requires reprioritization of energy and substrate metabolism in liver and skeletal muscle, resulting in hepatic ketogenesis and glucocorticoid-driven muscle catabolism, which are prevented by increasing food intake. This natriuretic-ureotelic, water-conserving principle relies on metabolism-driven extracellular volume control and is regulated by concerted liver, muscle, and renal actions.
EVALuna2:34241

High salt reduces the activation of IL-4- and IL-13-stimulated macrophages - Binger, Katrina J.; Gebhardt, Matthias; Heinig, Matthias; Rintisch, Carola; Schröder, Agnes; Neuhofer, Wolfgang; Hilgers, Karl Friedrich; Manzel, Arndt; Schwartz, Christian; Kleinewietfeld, Markus; Voelkl, Jakob; Schatz, Valentin; et al. (Journal of Clinical Investigation, 2015)
A high intake of dietary salt (NaCl) has been implicated in the development of hypertension, chronic inflammation, and autoimmune diseases. We have recently shown that salt has a proinflammatory effect and boosts the activation of Th17 cells and the activation of classical, LPS-induced macrophages (M1). Here, we examined how the activation of alternative (M2) macrophages is affected by salt. In stark contrast to Th17 cells and M1 macrophages, high salt blunted the alternative activation of BM-derived mouse macrophages stimulated with IL-4 and IL-13, M(IL-4+IL-13) macrophages. Salt-induced reduction of M(IL-4+IL-13) activation was not associated with increased polarization toward a proinflammatory M1 phenotype. In vitro, high salt decreased the ability of M(IL-4+IL-13) macrophages to suppress effector T cell proliferation. Moreover, mice fed a high salt diet exhibited reduced M2 activation following chitin injection and delayed wound healing compared with control animals. We further identified a high salt-induced reduction in glycolysis and mitochondrial metabolic output, coupled with blunted AKT and mTOR signaling, which indicates a mechanism by which NaCl inhibits full M2 macrophage activation. Collectively, this study provides evidence that high salt reduces noninflammatory innate immune cell activation and may thus lead to an overall imbalance in immune homeostasis.
EVALuna2:3819

Immune cells control skin lymphatic electrolyte homeostasis and blood pressure - Wiig, Helge; Schröder, Agnes; Neuhofer, Wolfgang; Jantsch, Jonathan; Kopp, Christoph; Karlsen, Tine V.; Boschmann, Michael; Goss, Jennifer; Bry, Maija; Rakova, Natalia; Dahlmann, Anke; Brenner, Sven; et al. (Journal of Clinical Investigation, 2013)
The skin interstitium sequesters excess Na+ and Cl- in salt-sensitive hypertension. Mononuclear phagocyte system (MPS) cells are recruited to the skin, sense the hypertonic electrolyte accumulation in skin, and activate the tonicity-responsive enhancer-binding protein (TONEBP, also known as NFAT5) to initiate expression and secretion of VEGFC, which enhances electrolyte clearance via cutaneous lymph vessels and increases eNOS expression in blood vessels. It is unclear whether this local MPS response to osmotic stress is important to systemic blood pressure control. Herein, we show that deletion of TonEBP in mouse MPS cells prevents the VEGFC response to a high-salt diet (HSD) and increases blood pressure. Additionally, an antibody that blocks the lymph-endothelial VEGFC receptor, VEGFR3, selectively inhibited MPS-driven increases in cutaneous lymphatic capillary density, led to skin Cl- accumulation, and induced salt-sensitive hypertension. Mice overexpressing soluble VEGFR3 in epidermal keratinocytes exhibited hypoplastic cutaneous lymph capillaries and increased Na+, Cl-, and water retention in skin and salt-sensitive hypertension. Further, we found that HSD elevated skin osmolality above plasma levels. These results suggest that the skin contains a hypertonic interstitial fluid compartment in which MPS cells exert homeostatic and blood pressure-regulatory control by local organization of interstitial electrolyte clearance via TONEBP and VEGFC/VEGFR3-mediated modification of cutaneous lymphatic capillary function.
EVALuna2:7617

Mild Salt-Sensitive Hypertension in Genetically Determined Low Nephron Number is Associated with Chloride but Not Sodium Retention - Benz, Kerstin; Schlote, Julia; Daniel, Christoph; Kopp, Christoph; Dahlmann, Anke; Schröder, Agnes; Cordasic, Nada; Klanke, Bernd; Hilgers, Karl Friedrich; Titze, Jens; Amann, Kerstin Ute (Kidney & Blood Pressure Research, 2018)
BACKGROUND/AIMS: One potential pathomechanism how low nephron number leads to hypertension in later life is altered salt handling. We therefore evaluated changes in electrolyte and water content in wildtype (wt) and GDNF+/- mice with a 30% reduction of nephron number. METHODS: 32 GDNF+/- and 36 wt mice were fed with low salt (LSD, 0.03%, normal drinking water) or high salt (HSD, 4%, 0.9% drinking water) diet for 4 weeks. Blood pressure was continuously measured by telemetry in a subgroup. At the end of the experiment and after standardized ashing processes electrolyte- and water contents of the skin and the total body were determined. RESULTS: We found higher blood pressure in high salt treated GDNF+/-compared to wt mice. Of interest, we could not confirm an increase in total-body sodium as predicted by prevailing explanations, but found increased total body and skin chloride that interestingly correlated with relative kidney weight. CONCLUSION: We hereby firstly report significant total body and skin chloride retention in salt sensitive hypertension of GDNF+/-mice with genetically determined lower nephron number. Thus, in contrast to the prevailing opinion our data argue for the involvement of non-volume related mechanisms.
EVALuna2:34423

Salt-dependent chemotaxis of macrophages - Mueller, Silke; Quast, Thomas; Schröder, Agnes; Hucke, Stephanie; Klotz, Luisa; Jantsch, Jonathan; Gerzer, Rupert; Hemmersbach, Ruth; Kolanus, Waldemar (PLoS ONE, 2013)
Besides their role in immune system host defense, there is growing evidence that macrophages may also be important regulators of salt homeostasis and blood pressure by a TonEBP-VEGF-C dependent buffering mechanism. As macrophages are known to accumulate in the skin of rats fed under high salt diet conditions and are pivotal for removal of high salt storage, the question arose how macrophages sense sites of high sodium storage. Interestingly, we observed that macrophage-like RAW264.7 cells, murine bone marrow-derived macrophages and peritoneal macrophages recognize NaCl hypertonicity as a chemotactic stimulus and migrate in the direction of excess salt concentration by using an in vitro transwell migration assay. While RAW264.7 cells migrated toward NaCl in a dose-dependent fashion, no migratory response toward isotonic or hypotonic media controls, or other osmo-active agents, e.g. urea or mannitol, could be detected. Interestingly, we could not establish a specific role of the osmoprotective transcription factor TonEBP in regulating salt-dependent chemotaxis, since the specific migration of bone marrow-derived macrophages following RNAi of TonEBP toward NaCl was not altered. Although the underlying mechanism remains unidentified, these data point to a thus far unappreciated role for NaCl-dependent chemotaxis of macrophages in the clearance of excess salt, and suggest the existence of novel NaCl sensor/effector circuits, which are independent of the TonEBP system.
EVALuna2:7634

Spooky sodium balance - Titze, Jens; Dahlmann, Anke; Lerchl, Kathrin; Kopp, Christoph; Rakova, Natalia; Schröder, Agnes; Luft, Friedrich C. (Kidney International, 2014)
Current teaching states that when sodium intake is increased from low to high levels, total-body sodium (TBNa) and water increase until daily sodium excretion again equals intake. When sodium intake is reduced, sodium excretion briefly exceeds intake until the excess TBNa and water are eliminated, at which point sodium excretion again equals intake. However, careful balance studies oftentimes conflict with this view and long-term studies suggest that TBNa fluctuates independent of intake or body weight. We recently performed the opposite experiment in that we fixed sodium intake for several weeks at three levels of sodium intake and collected all urine made. We found weekly (circaseptan) patterns in sodium excretion that were inversely related to aldosterone and directly to cortisol. TBNa was not dependent on sodium intake but instead exhibited far longer (>= monthly) infradian rhythms independent of extracellular water, body weight, or blood pressure. The findings are consistent with our ideas on tissue sodium storage and its regulation that we developed on the basis of animal research. We are implementing (23)Na-magnetic resonance imaging (MRI) to pursue open questions on sodium balance in patients. Our findings could be relevant to therapeutic strategies for hypertension and target-organ damage.
EVALuna2:3656